Research to the strength of High Speed Interior Permanent Magnet Synchronous Motor - Hu, Yusheng; Li, Liyi; Guo, Weilin; Zhang, Fang; Li, Guanghai (International Conference on Electrical Machines and Systems (Online), 2021)
The components of the rotor are subjected to a tremendous centrifugal force at high speed velocity. It can be cause damage deformation or even failure of the rotor structure. In this paper, a 300kW,30000r/min high speed interior permanent magnet synchronous motor(HS-IPMSM) is designed. The rotor rotational speed reached to 196m/s.The mechanical strength is analyzed by finite element method(FEM) and also the rotor over speeding testing is designed. The result of testing show that the rotor can operate reliably at 1.1 times of rated operating speed and the rotor strength content the design requirements.